High-resolution electric field and temperature distributions in positive streamers - Dijcks, Siebe; Kusýn, Lukáš; Janssen, Jesper; Bílek, Petr; Nijdam, Sander; Hoder, Tomáš (Frontiers in Physics, 2023)
In this work, we aim to take a detailed experimental picture of the positive streamer. We apply optical emission spectroscopy to the first negative system (FNS) of N2+ and the second positive system (SPS) of N2. Large, centimeter wide, and highly reproducible streamers are created in pure nitrogen and synthetic air, at pressures ranging from 33 to 266 mbar. Direct time resolved spectral imaging of the space charge layer resulted in spatiotemporal maps of the calculated reduced electric field strength (E/N) and rovibrational temperature in sub-nanosecond and sub-millimetre resolution. The E/N peaks at approximately 540 and 480 Td, directly in front of the space charge layer, for synthetic air and pure nitrogen respectively, as determined by using the intensity ratio method of FNS and SPS. A global model for pure nitrogen in PLASIMO uses the experimentally determined E/N distribution to draw a picture of the gas kinetics around the space charge layer passage. In addition, the results of the global model serve as a reference to interpret the rotational and vibrational temperatures obtained from experimental FNS and SPS emissions, which emphasize the streamers' non-equilibrium gas heating.